COVID‐19 impact on psychological outcomes of parents, siblings and children with intellectual disability: longitudinal before and during lockdown design - Bailey, T. (J Intellect Disabil Res, 2021)
BACKGROUND: Parents of children with intellectual disability (ID) report comparatively lower levels of well‐being than parents of children without ID. Similarly, children with ID, and to a lesser extent their siblings, are reported to show comparatively higher levels of behaviour and emotional problems. Psychological problems may be accentuated by restrictions associated with the COVID‐19 pandemic, due to increased social, caring and economic stressors and reduced social support. However, existing studies have not been able to examine the impact of COVID‐19 restrictions accounting for pre‐COVID levels of well‐being in these families. In a naturalistic design, we examined outcomes for parents, siblings and children with ID in a two‐wave longitudinal study where Wave 2 data were gathered for some families before and some during COVID‐19 restrictions. METHODS: Parents of children with ID who took part in a Wave 2 survey pre‐lockdown (n = 294) and during/post‐lockdown (n = 103) completed a number of measures about their well‐being and the behaviour and emotional problems of both their child with ID and their nearest‐in‐age sibling. These same measures had also been completed for all families 2–3 years previously in Wave 1 of the study. RESULTS: After accounting for covariates including family socio‐economic circumstances, pre‐lockdown and post‐lockdown groups did not differ on Waves 1 to 2 change for measures of parental psychological distress, life satisfaction, the impact of caregiving on their lives or perceived positive gains; nor child or sibling internalising or externalising behaviour problems. CONCLUSIONS: Findings of the current study indicate that during and shortly after the COVID‐19 lockdown in the United Kingdom, well‐being in families of children with an ID (as reported by parents) was at similar levels compared with prior to the lockdown period.